2003
DOI: 10.1300/j019v25n01_01
|View full text |Cite
|
Sign up to set email alerts
|

A Multicomponent Treatment Package to Increase Anger Control in Teacher-Referred Boys

Abstract: A manualized treatment package for anger control in boys ages 7 to 10 was investigated using a control group outcome design. The treatment package included modeling, rehearsal with self-talk problem-solving, daily report cards and a praise phase. At post-test treatment participants were significantly higher than controls on the Aggression Control factor of the Olweus Aggression Inventory (OAI) and the Compliment observation category. Control's scores were significantly higher than the treatment group's on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Topal (2021) stated that the psycho-education program is effective in increasing children's emotional regulation skills. Seay et al (2003) stated that children's anger control skills increased as a result of the Multi-Component Treatment to Increase Anger Control. Şekerci et al (2017) stated that the anger control program prepared according to the cognitive behavioural approach is effective in increasing anger control.…”
Section: Discussionmentioning
confidence: 99%
“…Topal (2021) stated that the psycho-education program is effective in increasing children's emotional regulation skills. Seay et al (2003) stated that children's anger control skills increased as a result of the Multi-Component Treatment to Increase Anger Control. Şekerci et al (2017) stated that the anger control program prepared according to the cognitive behavioural approach is effective in increasing anger control.…”
Section: Discussionmentioning
confidence: 99%
“…As an intervention tool, the DBRC has been used to rate social behaviors ranging from inappropriate verbalizations (e.g., Burkwist, Mabee, & McLaughlin, 1987) to aggression (e.g., Seay, Fee, & Holloway, 2003) as well as academic behaviors from work completion (e.g., Dougherty & Dougherty, 1977) to task accuracy (e.g., Blechman, Taylor, & Schrader, 1981). A review of the literature has indicated that use of the DBRC as a behavior-monitoring tool has not been significantly discussed or studied (see review by Chafouleas et al, 2002); however, results of early case studies have suggested that DBRCs can be used to monitor the effects of medication on children with attention-deficit/hyperactivity disorder by rating such behaviors as assignment completion and noncompliance (Pelham, 1993;Hyman et al, 1998).…”
Section: Dbrcmentioning
confidence: 99%